Analysis of Factors Affecting the Level of Public Knowledge of Sharia Bank Products : Case Study of Deli Serdang Regency - Basania Nasution; Ahmad Syakir; Wahyu Syarvina (Jurnal Manajemen Bisnis, 2024)
This research aims to describe the factors that influencing people’s insight into sharia banking products. Case study of Deli serdang district. This research using qualitative data analysis public knowledge of sharia banking products in the case study of kab. Serdang Deli. The data collection techniques used were direct interviews obtained from respondenst, researcher interviews with sources and direct observation of the research writer’s objects or places in the community of the Deli serdang district. And also from notes, books, aticels, government reports, books related to research, and to get actual data. Based on research results, not many people know what is a sharia bank and what products are available at sharia banks?. then from the results of interviews, most people are interested in transact with sharia banks, so there is a need for socialization from the banking side sharia in order to increase public knowledge about sharia banks as well as the availability of islamic banking institutions that are closer to public.